2021
DOI: 10.1088/1748-605x/ac0863
|View full text |Cite|
|
Sign up to set email alerts
|

The osteoimmunomodulatory effect of nanostructured TiF x /TiO x coating on osteogenesis induction

Abstract: Macrophages play a central role in the host response and the integration of implant materials. The nanostructured TiF x /TiO x coating (FOTi) on titanium surfaces has shown multiple properties, including antibacterial properties and bioactivity. However, little is known about the effects of these coatings on the regulation of macrophage activity and the subsequent immunomodulatory effects on osteogenesis. In this study, the behavior of macrophages on the FOTi samples was evaluated, and conditioned medium was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The titanium metal implant surface formed a nanostructure coating that stimulated macrophage elongation, promoted the production of proinflammatory cytokines, and induced macrophages to anti-inflammatory M2 phenotypes. This promote osteogenesis differentiation, such as cell adhesion, alkaline phosphatase activity, mineralization of the extracellular matrix, and raised the osteogenesis related gene expression ( Chen et al, 2021 ; Jiang et al, 2022 ). Zhao et al (2019) showed that the plasma electrolytic oxidation porous Mg-TiO 2 covered Ti surface not only promote osteoblast adhesion, proliferation, and differentiation, but also inhibited Staphylococcus engraftment and growth.…”
Section: Anti-infection and Multifunctional Materialsmentioning
confidence: 99%
“…The titanium metal implant surface formed a nanostructure coating that stimulated macrophage elongation, promoted the production of proinflammatory cytokines, and induced macrophages to anti-inflammatory M2 phenotypes. This promote osteogenesis differentiation, such as cell adhesion, alkaline phosphatase activity, mineralization of the extracellular matrix, and raised the osteogenesis related gene expression ( Chen et al, 2021 ; Jiang et al, 2022 ). Zhao et al (2019) showed that the plasma electrolytic oxidation porous Mg-TiO 2 covered Ti surface not only promote osteoblast adhesion, proliferation, and differentiation, but also inhibited Staphylococcus engraftment and growth.…”
Section: Anti-infection and Multifunctional Materialsmentioning
confidence: 99%